Meningkatkan Proses Pembelajaran Tematik Terpadu Menggunakan Model Two Stay Two Stray di Sekolah Dasar - Asni Santi Hasibuan; Zainal Abidin (Universitas Negeri Padang, 2020)
The purpose of this study is to describe the improvement of the integrated thematic learning process by using the two stay two stray model in grade IV of elementary school. This type of research is a classroom action research that uses qualitative and quantitative approaches. The subjects of this study were teachers and fourth grade elementary school students with a total of 28 people. The research procedure consisted of planning, implementing, observing, and reflecting. The results showed an increase in aspects of: a) RPP cycle I with an average of 79.16% and cycle II 94.44% b) Implementation of the aspects of the teacher cycle I with an average of 79.16% and cycle II 94, 44% whereas for the implementation of aspects of the first cycle students with an average of 79.16% and the second cycle 94.44%. The conclusion from the results of the research conducted is that using the Two Stay Two Stray model can improve the integrated thematic learning process in grade IV SDN 01 Ulak Karang Selatan.